2014
DOI: 10.1055/s-0034-1376398
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Breast Reconstruction in Thin Patients: The Impact of Low Body Mass Indices

Abstract: Patients undergoing autologous breast reconstruction have been shown to have higher overall rates of long-term satisfaction when compared with patients with implant-based reconstructions.1-5 While there is a national trend toward increasing rates of implant-based breast reconstructions, certain centers show microsurgical breast reconstruction is being increasingly performed for both therapeutic and prophylactic indications. [6][7][8][9][10] This rise in the use of autologous tissue for breast reconstruction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Autologous breast reconstruction in thin patients is often challenging due to an apparent lack of adequate donor sites. Previous studies indicated TMG flap breast reconstruction to be more likely performed in slim and normal weight patients compared with those having abdominal-based breast reconstruction [ 6 , 13 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autologous breast reconstruction in thin patients is often challenging due to an apparent lack of adequate donor sites. Previous studies indicated TMG flap breast reconstruction to be more likely performed in slim and normal weight patients compared with those having abdominal-based breast reconstruction [ 6 , 13 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, an adequate TMG flap volume with a mean flap weight of 330 g could be harvested from the medial thigh donor site in our patients, where the proportional excess of soft tissue can be significant compared to other parts of the body [ 20 ]. In this context Weichman et al investigated the impact of low BMI on the feasibility of performing autologous breast reconstruction with various flaps from the lower abdomen, bottom and thigh [ 19 ]. Similar to our study, the mean flap weight per breast used was 387 g in low–normal (18.5–22 kg/m 2 ) weight patients and 367 g in high–normal (22–25 kg/m 2 ) weight patients.…”
Section: Discussionmentioning
confidence: 99%
“…The deep inferior epigastric perforator (DIEP) flap derived from the abdomen is considered the first choice in autologous breast reconstruction with success rates of up to 99% 2,3 . However, patients with insufficient abdominal tissue or previous abdominal surgeries require alternative donor sites for tissue harvest 4 . Moreover, some patients might refuse the procedure to avoid the visible transverse donor site scar on the abdomen.…”
Section: Introductionmentioning
confidence: 99%
“…First outlined in 1992 by Yousif et al, 5,6 the TMG flap includes a horizontal skin island based on the transverse course of perforators arising from the gracilis muscle and the pliant soft tissue surplus from the medial thigh optimizing former limitations of the free gracilis musculocutaneous flap including flap volume and skin island vascularity. Due to excellent breast results with almost natural contour and shape, the TMG flap has gained popularity over the last few years 4,7,8 . Some authors even advertised the TMG flap as a first‐line option in slim to normal‐weight patients 7,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Various free flaps for autologous breast reconstructions are available and now represent routine procedures for breast reconstruction after skin-sparing or conventional mastectomy and breast conserving treatment. The deep inferior epigastric perforator (DIEP) flap became a gold standard [ 4 ] for breast reconstruction in patients with sufficient amounts of abdominal donor tissue [ 7 ]. In patients who do not offer enough abdominal donor tissue for reconstruction because of low body mass index or where the deep inferior epigastric vessels might have been damaged by prior abdominal surgeries, a vast number of alternative free flaps are available.…”
Section: Introductionmentioning
confidence: 99%